Pundits, Trinidad, B.W.I. - (:unkn) unknown (Canning and Co. Ltd, 2008)
Two East Indian holy men sit in the shade of a shed. One of the men is cradling a book and there is a carriage behind them.
Colour: White, green and brown hues; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Hindu priests--Trinidad and Tobago; Tilaks--Trinidad and Tobago; Body marking--Religious aspects--Hinduism; East Indians--Trinidad and Tobago; Men--Trinidad and Tobago; Ethnic costume--India; Clothing and dress--Trinidad and Tobago; Necklaces--India; Men's clothing--India; Turbans--India; Headgear--India; Sheds--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Trinidad and Tobago; [1910]; Garages--Trinidad and Tobago